Analysis of Pre-Service Science Teachers’ Heuristic Reasoning Processes about Hydrogen Bonding - Gülen Önal Karakoyun; Erol Asiltürk (Universitas Pendidikan Indonesia, 2020)
The purpose of this research was to determine the heuristics used by pre-service science teachers in understanding the details of hydrogen bonding. The reasoning processes demonstrated were evaluated based on ten heuristic models suggested by Talanquer (2014). Phenomenographic assessment of the 30 participants indicated that all ten heuristics were utilized to make interpretations about hydrogen bonding. It was found that most students used short-cut strategies rather than efficient analytical reasoning processes. A total of 12 answer patterns were determined based on the answers of the participants. The percentage of students who gave the correct answer was low. The frequency sequencing of participants' heuristics demonstrated in this study was fluency, associative activation, recognition, one-reason decision making, attribute substitution, overconfidence, surface similarity, generalization, rigidity, and affect.